The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.radcr.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric milk protein allergy causing hepatic portal venous gas: Case report

Abstract: Hepatic portal venous gas (HPVG) is a rare imaging finding in infants and usually indicative of a severe disease process such as necrotizing enterocolitis, bowel ischemia, or bowel wall rupture / infarction. The diagnosis of HPVG may have serious implications such as parenteral nutrition, antibiotics and even surgery. In this case, we present an 8-week-old male with a history of prematurity presenting with HPVG, later concluded to be caused by milk protein allergy. Milk protein allergy is a rare cause of HPVG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…These children might present with emesis, irritability or bloody diarrhea, and US is occasionally requested to assess for pyloric stenosis or intussusception. Sonographic findings include diffuse bowel wall thickening and hypervascularity, and less commonly pneumatosis intestinalis [34,35]. Because of potential clinical and radiologic overlap with necrotizing enterocolitis, an awareness of patient history is critical to recognize the benignity of the condition and avoid unnecessary intervention.…”
Section: Other Immune-mediated Conditionsmentioning
confidence: 99%
“…These children might present with emesis, irritability or bloody diarrhea, and US is occasionally requested to assess for pyloric stenosis or intussusception. Sonographic findings include diffuse bowel wall thickening and hypervascularity, and less commonly pneumatosis intestinalis [34,35]. Because of potential clinical and radiologic overlap with necrotizing enterocolitis, an awareness of patient history is critical to recognize the benignity of the condition and avoid unnecessary intervention.…”
Section: Other Immune-mediated Conditionsmentioning
confidence: 99%
“…However, less severe disease processes, such as CPMA, can also cause PI. 5 We made this diagnosis based on the following findings: (1) gastrointestinal symptoms started after 1 month of age, and typically, NEC occurs within the first week after birth 5 ; (2) prematurity is a reported risk factor for CPMA 1 ;…”
Section: Descriptionmentioning
confidence: 99%
“…To avoid unnecessary interventions, benign causes of PI should be considered if severe systemic disease is not obvious. 5 In CPMA, disease presentation and symptom severity are diverse, 2 but they Figure 1 Pneumatosis intestinalis.…”
Section: Descriptionmentioning
confidence: 99%
“…This nding has historically been considered a poor prognosis and life-threatening factor in neonates with NEC for a long time, as it represents a late sign of intestinal ischemia and a relative indicator for surgical intervention [2][3][4]. With the development of radiology, more and more recent literatures have reported that PVG is not only present in neonates with intestinal ischemia, but also in those with benign condition, such as bowel in ammation, food allergies and so on [5][6][7]. Moreover, the strategy of PVG alone as an indication for surgery has been questioned and challenged [8][9][10].…”
Section: Introductionmentioning
confidence: 99%